TaARPC3, Contributes to Wheat Resistance against the Stripe Rust Fungus - Qi, Tuo; Wang, Juan; Sun, Qixiong; Day, Brad; Guo, Jun; Ma, Qing (Frontiers in Plant Science, 2017)
The actin cytoskeleton participates in numerous cellular processes, including less-characterized processes, such as nuclear organization, chromatin remodeling, transcription, and signal transduction. As a key regulator of actin cytoskeletal dynamics, the actin related protein 2/3 complex (Arp2/3 complex) controls multiple developmental processes in a variety of tissues and cell types. To date, the role of the Arp2/3 complex in plant disease resistance signaling is largely unknown. Herein, we identified and characterized wheat ARPC3, TaARPC3, which encodes the C3 subunit of the Arp2/3 complex. Expression of TaARPC3 in the arc18 mutant of Saccharomyces cerevisiae Δarc18 resulted in complementation of stress-induced phenotypes in S. cerevisiae, as well as restore wild-type cell shape malformations. TaARPC3 was found predominantly to be localized in the nucleus and cytoplasm when expressed transiently in wheat protoplast. TaARPC3 was significantly induced in response to avirulent race of Puccinia striiformis f. sp. tritici (Pst). Knock-down of TaARPC3 by virus-induced gene silencing resulted in a reduction of resistance against Pst through a specific reduction in actin cytoskeletal organization. Interestingly, this reduction was found to coincide with a block in reactive oxygen species (ROS) accumulation, the hypersensitive response (HR), an increase in TaCAT1 mRNA accumulation, and the growth of Pst. Taken together, these findings suggest that TaARPC3 is a key subunit of the Arp2/3 complex which is required for wheat resistance against Pst, a process that is associated with the regulation of the actin cytoskeleton.